Profitabilitas, Corporate Social Responsibility, Good Corporate Governance dan Ukuran Perusahaan terhadap Nilai Perusahaan Manufaktur di Indonesia - Astiti, Ni Putu Yeni (Ekonomis: Journal of Economics and Business, 2024)
The value of a company can basically be measured through several aspects, one of the proxy that can be used is the price book value (PBV) or comparing the price of shares per share with the book value per share. This population study is a manufacturing company listed on the Indonesian Stock Exchange on the grounds that more manufacturing companies have an impact on the surrounding environment as a result of operational activities carried out with a population of 150 companies. Sampling using purposive sampling is the technique of taking samples with specific consideration. The sample for this study is 50 companies with 3 years of observation and a total of 150 observations. Profitability has a positive impact on the value of the company. CSR has a negative impact on company value. GCG positively affects company value and company size does not affect the company's value.